(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Successful entrepreneurs are usually modeled ascombinations of innovators (with creative and innovative flair) and managers(with strong general management skills, business know-how, and sufficientcontacts). The article is aimed at the impact of entrepreneurialinnovation promoting entrepreneurship among young people. The results find outand confirmed that the main factor of entrepreneurial intention is innovationand others are personality traits, attitude towards entrepreneurship,behavioral control, and they can be developed during the study process.